Impact of Covid-19 on the Mental Health of Delta State University students, Nigeria - Ominde, Beryl; Jaiyeoba-Ojigho, Jennifer Efe; Igbigbi, Patrick Sunday (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: The coronavirus disease 2019 (COVID-19) pandemic has led to a substantial psychological burden among students. This study aimed at evaluating the impact of the COVID-19 on the mental health of university students and determining the prevalence of anxiety and depression. Methods: This cross-sectional descriptive study utilized an online questionnaire sent to students in the Faculty of Basic Medical Sciences, Delta State University after ethical approval. The Generalized Anxiety and Disorder Scale-7 (GAD-7) and Patient Health Questionnaire-9 (PHQ-9) scores were analyzed using the Statistical Package of Social Sciences and expressed using descriptive statistics and percentages. An independent t-test was used to determine the gender differences in the GAD-7 and PHQ-9 scores while Pearson’s correlation was used to establish a relationship between these scores with age. Results: The 259 respondents comprised 118, 45.6% males and 141, 54.4% females with an average age of 21.50±2.04 years. The majority (149, 57.5%) were aged 21-25 years. The scores did not show significant differences in age and gender. Moderate to severe anxiety and depression was established in 22.4% and 28.2% of the respondents respectively. Conclusion: This study has shown that the prevalence of anxiety and depression due to the pandemic bears no relationship with age and gender. This is however different from previous reports due to the differences in the sample size, resource setting, timing of the study, and the courses the students studied.